Factors influencing the application of nature as inspiration for sustainability‐oriented innovation in multinational corporations. (6th July 2020) - Mead, Taryn; Jeanrenaud, Sally; Bessant, John
Abstract: Nature‐inspired innovation (NII) is an increasingly common innovation strategy, yet little is known about its implementation within corporate innovation settings. This paper asks what factors influence the application of NII in corporate contexts. It combines theoretical perspectives from innovation adoption and sustainability‐oriented innovation to explore factors that influence the implementation of NII. Six case studies of multinational corporations applying NII were analyzed, using data collected through semistructured interviews ( N = 45), a review of internal project documents, and publicly available materials. Results indicate that successful implementation depends upon the characteristics of the innovation context, decision‐making units, and the innovation itself, such as an advanced organizational progression of corporate sustainability, senior leadership support of NII, design expertise within innovation teams, flexible innovation management processes, and collaboration with outside enabling stakeholders. NII should be viewed as a longer‐term investment in developing organizational sustainability culture rather than a one‐off approach to innovation.